ВИЗНАЧЕННЯ СФОРМОВАНОСТІ МОТИВАЦІЙНОГО КОМПОНЕНТУ ЯК СКЛАДОВОГО ЕЛЕМЕНТУ ПІЗНАВАЛЬНОЇ АКТИВНОСТІ (Педагогіка вищої та середньої школи, 2007)
In clause the author traces opportunities level form motivation in the process of training history, causes low interest schoolboys and teachers are analysed.